2023
DOI: 10.3389/fendo.2023.1112363
|View full text |Cite
|
Sign up to set email alerts
|

The impact of oxidative stress-induced mitochondrial dysfunction on diabetic microvascular complications

Abstract: Diabetes mellitus (DM) is a metabolic disease characterized by chronic hyperglycaemia, with absolute insulin deficiency or insulin resistance as the main cause, and causes damage to various target organs including the heart, kidney and neurovascular. In terms of the pathological and physiological mechanisms of DM, oxidative stress is one of the main mechanisms leading to DM and is an important link between DM and its complications. Oxidative stress is a pathological phenomenon resulting from an imbalance betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(19 citation statements)
references
References 248 publications
2
11
0
Order By: Relevance
“…In this sense, our study shows alteration of oxidative stress and differential relaxant responses to CCh and SNP; it is necessary to mention that our findings are in concordance with previous studies. 43,68,69 Taken together, our results and previous studies suggest that increasing oxidative stress affects mainly the endothelium instead of the smooth muscle, affecting production and not the NO pathway signaling. However, H 2 S is a scavenger of ROS because of its reductive potential acting as an antioxidant.…”
Section: Discussionsupporting
confidence: 82%
“…In this sense, our study shows alteration of oxidative stress and differential relaxant responses to CCh and SNP; it is necessary to mention that our findings are in concordance with previous studies. 43,68,69 Taken together, our results and previous studies suggest that increasing oxidative stress affects mainly the endothelium instead of the smooth muscle, affecting production and not the NO pathway signaling. However, H 2 S is a scavenger of ROS because of its reductive potential acting as an antioxidant.…”
Section: Discussionsupporting
confidence: 82%
“…Also, PA caused oxidative stress to BEECs, as demonstrated by the significantly increase in intracellular and mitochondrial ROS levels, the higher MDA content and decrease in SOD activity. By combining the swelling and cristae rupture of mitochondria, we confirmed that the oxidative stress induced by PA may damage the mitochondria [29].…”
Section: Discussionsupporting
confidence: 54%
“…Release of CytC usually accompanies a decrease in ΔΨm. 32 Western blot revealed that exposure to 400 μg/ml UCNP for 24 h significantly increased Cyt C protein levels in SGC-7901 cells compared to control cells ( p < 0.05; Figure 3D). The PI3K-Akt signaling pathway regulates tumor cell proliferation and resistance to chemotherapy.…”
Section: Resultsmentioning
confidence: 97%